2020
DOI: 10.1002/pmrj.12296
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Long Distance Road Runners and Trail Runners in Achilles Tendon Structure and Jumping and Balance Performance

Abstract: BackgroundLoad and joint kinematics change with differences in running surface. Running regularly on trails compared to roads might influence the load on the Achilles tendon and its adaptations, along with other factors such as balance, strength, and proprioception.ObjectiveTo investigate Achilles tendon structure and functional tests in road and trail runners.DesignCross‐sectional study.SettingLaboratory, sport sciences college.ParticipantsThe study included 26 road and 17 trail runners who run at least three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…All prior UTC studies have identified that the Achilles tendon consists of predominantly echo‐types I and II and minimal levels of echo‐types III and IV. Several previous studies have shown a reciprocal interplay between Echo‐types I and II 18,22–24 . Dar et al found lower levels of echo‐type I and higher levels of echo‐type II in road runners when compared to trail runner 23 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…All prior UTC studies have identified that the Achilles tendon consists of predominantly echo‐types I and II and minimal levels of echo‐types III and IV. Several previous studies have shown a reciprocal interplay between Echo‐types I and II 18,22–24 . Dar et al found lower levels of echo‐type I and higher levels of echo‐type II in road runners when compared to trail runner 23 .…”
Section: Discussionmentioning
confidence: 97%
“…Several previous studies have shown a reciprocal interplay between Echo‐types I and II 18,22–24 . Dar et al found lower levels of echo‐type I and higher levels of echo‐type II in road runners when compared to trail runner 23 . It has yet to be determined whether it is preferential to have higher levels of echo‐type I or II.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding AT, Wiesinger et al (36) and Kongsgaard et al (37) studied the differences of the AT morphologic characteristics between runners and other sport athletes. Differences in AT morphologic characteristics were also analysed in relation to other aspects: road runners and trail runners (38), running performance (39), leg dominant side (40) and nationality (Kenyan versus Japanese runners) (41). Finally, other subject characteristics such as sex, body mass, height, body mass index and running experience (35,40) were also studied in relation to the AT morphologic characteristics.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…It would be worth analysing whether tendon morphological characteristics is dependent upon training level within the same sport. Other possible influencing factors that were studied but that did not show a significant relationship with the morphological characteristics of the connective tissue were running surface (38), running performance (39) and dominant side (40). The studies that have evaluated these aspects are few, so the scientific evidence is limited.…”
Section: Sample Characteristicsmentioning
confidence: 99%